"I have three years old". (24th June 2019) - Nicoladis, Elena
Abstract : There is evidence that adults store fixed expressions as both units and compositionally in their mental lexicon. According to Usage-Based theories, children initially acquire memorized chunks of language (fixed expressions) and gradually abstract productive patterns (compositional representation). This study addresses whether a French-English bilingual child has compositional representation of fixed expressions using diary data on her use of fixed expressions requiring the verb to be in English and avoir 'to have' in French between the ages of 3;4 and 4;3. According to Usage-Based theories, children should learn these fixed expressions as fixed expressions and therefore show little cross-linguistic influence. However, from the earliest age under study, this child occasionally used the non-target verb, suggesting that her representation of these fixed expressions was already also compositional.